Analisis Hidrograf Satuan Sintetik Limantara Berdasarkan Karakteristik Morfometri di DAS Klawoguk - Anif Farida; Achmad Rusdi; Hendrik Pristianto (Yayasan Literasi Sains Indonesia, 2026)
This study aims to analyze the characteristics of the Limantara Synthetic Unit Hydrograph (SUH) based on morphometric parameters in the Klawoguk Watershed. Watershed morphometric parameters were extrated from Digital Elevation Model (DEM) and river network maps using Geographic Information System. The time lag (Tg), rainfall time (Tr), time to peak (Tp), and peak discharge (Qp) values ​​in each sub-watershed were determined as input for the Limantara SUH. The results showed that the morphometric characteristics of the Klawoguk Watershed have an influence on the Limantara SUH. The variability in watershed area, the length of the main river, the length of the river to the center of gravity of the watershed, and the slope of the river cause differences in the values ​​of Tg, Tr, Tp, and Qp. Sub-watershed 5 has the highest peak discharge of 0,558 m³/s and a peak time of 1,308 hours while the sub-watershed 2 has the lowest peak discharge of 0,231 m³/s. The hydrographs of all sub-watersheds also show a rapid increase in discharge (rising limb) and a slower decrease in discharge (recession limb), indicating a greater influence of surface runoff than infiltration. The larger the watershed area and the length of the main river, the resulting hydrograph has a longer recession time with a higher peak discharge value. Conversely, a steeper river slope results in a faster flow response. This indicates that the Limantara HSS method describes the characteristics of the watershed's hydrological response based on morphometric parameters.